Multidrug Resistant Escherichia coli and Klebsiella pneumoniae Causing Urinary tract Infection in Pregnant Women - Qadeer, Naveen; Durrani, Muhammad Asif; Iqbal, Syed Manzoor (International Journal of Pathology, 2018)
Objective: Identify the multidrug resistant Escherichia coli and Klebsiella pneumoniae occurring in pregnantwomen with urinary tract infection.Materials and Methods: A total of 200 clean catch midstream urine specimens (MSU) were collectedfrom pregnant women in a sterile container. Specimens were then inoculated on Blood agar, Mac-Conkey agar and cysteine lactose electrolyte deficient (CLED) agar medium. Uropathogens were identifiedby using battery of tests. Antimicrobial susceptibility was determined by Kirby Bauer disc diffusionmethod as per Clinical and Laboratory Standard Institute (CLSI) guideline.Results: E. coli constituted 39.70% of bacterial population followed by K. pneumonia 20.58%. Antimicrobialtests, of isolated strains showed 92.68% sensitivity to imipenem, 87.8% to piperacillin/ tazobactamwhile 100% resistance to ampicillin.Conclusion: E. coli remained the most common cause of UTI followed by K. pneumonia. Imepenemshowed high sensitivity to UTI as compared to piperacillin/ tazobactam in our set up.